Two novel trimethylsulfonium salts with polymeric [SbCl4]−n or [CdCl3]−n anions. Issue 2 (10th January 2014) - Liu, Ming‐Liang; Kong, Li‐Hui
<x xml:space="preserve">Abstract</x> The title organic–inorganic hybrid salts poly[trimethylsulfonium [[dichloridoantimony(III)]‐di‐μ‐chlorido]], (C3H9S)[SbCl4]n, (I), and catena‐poly[trimethylsulfonium [cadmium(II)‐tri‐μ‐chlorido]], (C3H9S)[CdCl3]n, (II), consist of trimethylsulfonium cations and polymeric [SbCl4]−n or [CdCl3]−n anions. The central metal atoms are coordinated by six Cl atoms, forming an anionic [SbCl4]−n three‐dimensional framework (two of the four bridging chloride anions are located on two different centres of inversion) or anionic [CdCl3]−n one‐dimensional chains. The trimethylsulfonium cation of (II) is disordered over two sets of sites in a 0.791 (4):0.209 (4) ratio. All the anions are linked by trimethylsulfonium cations through weak C—H...Cl hydrogen bonds to form three‐dimensional structures.